Saminism As a Defense of Simple Architecture Samin Tribe in the Midst of Disruption Era - Estu Ajeng Wulaningtyas; Melindah Theresya (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The Samin tribe is one of the Indonesian tribe who occupies the border area between East Java and Central Java, exactly at Blora and Bojonegoro District. The Samin tribe has a tenet named Saminism, a thought about the discipline of simplicity. The simplicity can be found in their pure life and not infatuate on the development of the outside world. Moreover, it’s also applied to the form of Samin tribe’s house which has simple ornaments or even there are no ornaments that decorate their house. Even when most people has moved forward with this technological sophistication, Saminism still attached to its adherents. Then, is this simplicity has defended the look of Samin tribe’s culture? This research is a descriptive – qualitative research that was began with data collection, then continued by data processing or analysis, and deduced the results of the data. The result from this research is how Samin tribal society survived in the middle of disruption era by attaching to the thoughts of Saminism which is still could be found today.